A PREDICTIVE MODEL FOR NON-INVASIVE EVALUATION OF LIVER FIBROSIS IN PATIENTS WITH CHRONIC HEPATITIS VIRUS INFECTION - A. A. Ostanin (SPb RAACI, 2014)
Abstract. This study was conducted to develop a predictive model including routinely available laboratory tests to reflect the histological liver fibrosis stage in patients with chronic hepatitis virus infection (HVI). The «training» (preliminary) cohort included 37 healthy volunteers without liver fibrosis (F0) and 126 patients with minimal (F1/2, n = 40) and significant/advanced (F3, n = 39) fibrosis and histological cirrhosis (F4, n = 47). It was revealed that several routine clinical/biochemical parameters (erythrocyte sedimentation rate, platelet count, prothrombin time [PT], serum level of albumin [Alb], bilirubin, aspartate aminotransferase [AST], thymol test) and immunological features (IgA, IgG) as well special fibrosis markers (ММР-9, TIMP-1) significantly correlated with severity of liver fibrosis (Spearman’s rank correlation coefficient 0.45-0.69; p < 0.0001). To select predictive factors contributing to discrimination of the fibrosis stage, we performed a stepwise logistic multivariate regression of the laboratory variables in F1/2 vs F3, and F3 vs F4 patients, respectively. Based on the multiple regression model, we derived a novel Integral Index of Fibrosis (IIF) defined by five biochemical parameters (PT, glucose, Alb, AST, lactate dehydrogenase). IIF was applied to the validation cohort comprised of 84 patients with chronic HVI (F1/2 n = 42; F3 n = 19; F4 n = 23) to test its diagnostic accuracy. Corresponding values of IIF allow a reliable prediction of fibrosis stages (F1/2 vs F3 vs F4) with a diagnostic accuracy of 86%; with a positive predictive value (PPV is the percentage of positive tests that are truly positive) of 94%; and with a negative predictive value (NPV is the percentage of negative tests that are truly negative) of 91.7%. In conclusion, our study showed that the Integral Index of Fibrosis consisting of five routinely available laboratory tests provides clinically useful information regarding different liver fib rosis stages among patients with chronic hepatitis virus infection. (Med. Immunol., vol. 10, N 4-5, pp 405-414).